Use of oxalis corniculata paste on dentinal tubule blockage. - Pandey, Nashib (2021)
Executive Summary: Dentinal hypersensitivity, a global burden in dentistry is in increasing trend. Among the various products to treat dentinal hypersensitivity, oxalate-based toothpaste and mouthwashes have been proven successful in reducing the effects by occluding open dentinal tubules. Potassium oxalate (KO) has even been approved by the US Food and Drug Administration to treat dentine hypersensitivity. A common herb found abundantly in Nepal which contains oxalate as a major constituent will be used to prepare the paste to be used by the patients in treating dentinal hypersensitivity. This project aims to assess the dentinal tubule blocking property of Oxalis corniculate using extracted tooth, in the hope to be used as dentine hypersensitivity relieving agents in the future. Twenty-three teeth indicated for extraction along with the demographic details has been collected from the Department of Oral & Maxillofacial Surgery with patient consent. The collected teeth have been cleaned and fixed with 10% formalin. One mm section of the collected tooth has been made and stored in commercially available artificial saliva (Wet mouth). Dentin exposure will be made on the sectioned tooth where the Oxallis corniculta paste application will be done for 4 weeks daily topically with a finger. Scanning Electron Microscope (SEM) observation for the percentage of dentinal tubule blockage will be carried out. The results obtained from this study could be a landmark in determining appropriate at-home care regimens for patients with hypersensitivity. Keywords: Dentinal Hypersensitivity, Hypersensitivity, Oxallis Corniculata paste